Autonomy and competence satisfaction as resources for facing chronic pain disability in adolescence: a self-determination perspective: Original article. Issue 3 (16th March 2021) - Riggenbach, A.; Amouroux, R.; Van Petegem, S.; Tourniaire, B.; Tonelli, A.; Wiener, S.; Hofer, M.; Antonietti, J. Ph.
ABSTRACT: This study aimed to test empirically the developmental goal pursuit model of paediatric chronic pain, which draws upon Self-Determination Theory for understanding risks and resources for living with chronic pain. This study examined the relationship between basic psychological need satisfaction (i.e. the satisfaction of the needs for autonomy, relatedness and competence) and the fear-avoidance model of pain in adolescents suffering from chronic pain. Hundred and twenty adolescents (mean age = 14.52, 71.6% female), receiving treatment through paediatric pain centres for chronic pain, were enrolled. Adolescents completed measures of basic psychological need satisfaction, fear and avoidance of pain, and pain-related functional impairment. Path analyses model indicated that higher levels of autonomy and competence satisfaction were associated with lower levels of functional disability, through the mediation of fear and avoidance of pain. Relatedness satisfaction was not significatively related to fear of pain, avoidance, and functional disability. The integration of Self-Determination Theory in the paediatric pain literature may further our understanding of potential resources for decreasing functional disability in children living with chronic pain.